(untitled) - Murphy, Cillian; 1974-; Wilkinson, Tom; 1948-; 1944-2019.; Watanabe, Ken; 1959-; Hauer, Rutger; Nolan, Christopher; 1970-; Bale, Christian; 1974-; et al. (Burbank, Calif., 2005)
In an effort to deal with the death of his parents years before, a young Bruce Wayne travels the world in search of answers and comes back to Gotham City with the skills necessary to fight the injustices around him.
Keywords: Film and video adaptations; Kane, Bob; Batman (Fictitious character); Drama; Heroes; Drama; Video recordings for the hearing impaired; Feature films; Action and adventure films; Superhero films